Mapping the Intellectual Structure of Item Response Theory and Rasch Model Applications in Physics Education Assessment: A Scopus-Based Bibliometric Analysis - Haeruddin Haeruddin; Delthawati Isti Ratnaningtyas; Muhammad Jarnawi; Syamsuriwal Syamsuriwal; Rudi Santoso (Universitas Lambung Mangkurat, 2026)
Assessment in physics education requires valid and reliable measurement instruments capable of accurately representing students’ cognitive abilities, including conceptual understanding, scientific reasoning, and problem-solving skills. Over the past decades, instrument validation has shifted from Classical Test Theory to modern probabilistic measurement models, particularly Item Response Theory (IRT) and the Rasch model. Despite the growing application of these models in physics education research, the expanding literature remains thematically and methodologically fragmented, limiting a comprehensive understanding of the field’s intellectual development. Therefore, this study aims to map the intellectual structure and research trends of IRT and Rasch model applications in physics education assessment. This study employed a bibliometric research design using 243 Scopus-indexed publications published between 2001 and 2026. Bibliographic metadata were retrieved using Publish or Perish and analyzed using the Bibliometrix package in RStudio and VOSviewer to examine publication trends, influential sources, collaboration networks, and keyword co-occurrence patterns. The results reveal substantial growth in publications, increasing by more than 1,150% over the past two decades. Five major thematic clusters were identified: measurement frameworks, psychometric modeling, validity and fairness, instrument development and technology, and learning progression. Emerging themes such as computational thinking, digital instrument development, and multidimensional assessment indicate a shift toward competency-based and technology-supported assessment practices. Overall, the findings reveal the intellectual structure and research trends of IRT and Rasch model applications in physics education assessment, demonstrating their growing role as central methodological frameworks in contemporary assessment research. These findings also provide directions for future research, particularly in developing multidimensional Rasch-based instruments and technology-enhanced assessment systems in physics education